Ablation of Vti1a/1b Triggers Neural Progenitor Pool Depletion and Cortical Layer 5 Malformation in Late-embryonic Mouse Cortex. (21st May 2021) - Sokpor, Godwin; Rosenbusch, Joachim; Kunwar, Ajaya J.; Rickmann, Michael; Tuoc, Tran; Rizzoli, Silvio O.; Tarabykin, Victor; von Mollard, Gabriele Fischer; Krieglstein, Kerstin; Staiger, Jochen F.
Highlights: Neurogenic progenitor cells are lost in the perinatal mouse cortex lacking Vti1a/1b SNAREs. The E18.5 cortical layer 5 (L5) is disorganized due to knockout of Vti1a/1b in mouse. Vti1a/1b ablation leads to overt apoptosis of Ctip2-expressing L5 neurons in the perinatal mouse cortex. Contribution of L5 neurons to formation of corpus callosum and pyramidal tract is reduced in the Vti1a/1b-null mouse cortex. Abstract: Cortical morphogenesis entails several neurobiological events, including proliferation and differentiation of progenitors, migration of neuroblasts, and neuronal maturation leading to functional neural circuitry. These neurodevelopmental processes are delicately regulated by many factors. Endosomal SNAREs have emerged as formidable modulators of neuronal growth, aside their well-known function in membrane/vesicular trafficking. However, our understanding of their influence on cortex formation is limited. Here, we report that the SNAREs Vti1a and Vti1b (Vti1a/1b) are critical for proper cortical development. Following null mutation of Vti1a/1b in mouse, the late-embryonic mutant cortex appeared dysgenic, and the cortical progenitors therein were depleted beyond normal. Notably, cortical layer 5 (L5) is distinctively disorganized in the absence of Vti1a/1b. The latter defect, coupled with an overt apoptosis of Ctip2-expressing L5 neurons, likely contributed to the substantial loss of corticospinal and callosal projections in the Vti1a/1b-deficient mouse brain. These findings suggest that Vti1a/1b serve key neurodevelopmental functions during cortical histogenesis, which when mechanistically elucidated, can lend clarity to how endosomal SNAREs regulate brain development, or how their dysfunction may have implications for neurological disorders.